Land Agency in Realizing a Systematic Land Registration Program Complete - Kautsar, Alfiya; Anzar , Anzar; Arsyad, Nasrullah (Faculty of Law, Universitas Muslim Indonesia, 2025)
Study This aiming For know the role of the National Land Agency in realize Systematic Land Registration Complete (PTSL) in Makassar City and find out obstacles faced by the National Land Agency in implementation Systematic Land Registration Complete (PTSL) in Makassar City. The research method used is method study empirical . The results of study This that is , to show role of the Land Agency in realizing the Systematic Land Registration program Complete in Makassar City , namely stage planning , determination location , preparation , formation and establishment committee adjudication Systematic Land Registration Complete (PTSL) and units assignments , counseling , collection of physical data and legal data , legal data research and proof rights , announcement of physical data and legal data as well as its ratification , confirmation conversion , recognition rights and grants rights , bookkeeping rights , publishing certificate right on land , documentation and handover results activity as well as reporting . Then , the obstacles faced by the Makassar City National Land Agency in realize Systematic Land Registration Complete that is moving domicile expert inheritance , letter information expert the heirs who have move domicile and sufficient registration process complex . Recommendations study This It is expected that the Makassar City Land Office will running a Systematic Land Registration program Complete (PTSL) in collaboration with public Give socialization so that speed up this program walk and give certainty law and protection law right on land public based on principle simple , cheap , fast , smooth , safe , fair , equitable and open as well as accountable , so that can increase welfare and prosperity society and the country's economy , as well as reduce and prevent disputes and conflicts land .